Management Accounting Practices’ Impact on Firm Performance - Habibah, Annisa Nur; Fisher, Bobby (Dinasti Publisher, 2025)
This study seeks to examine the impact of management accounting methods on the performance of businesses in the South Jakartan manufacturing sector. To gather quantitative data, 115 managers from various divisions were surveyed. According to regression analysis, strategic management accounting, performance evaluation systems, budgeting systems, cost systems, and decision support systems are some of the management accounting approaches that have a significant impact on business performance. Decision support and performance evaluation tools have a particularly positive impact, despite the negative effects of budgeting methods. The study contributes to illustrating why efficient management accounting techniques are essential for improved business performance and more data for managers to use when making strategic choices